Molecular cloning, expression and functional analysis of foxl2 from Chinese sturgeon (Acipenser sinensis) in relation to sex differentiation - Hu, Yacheng; Tan, Ruihua; Li, Yang; Shu, Tingting; Yang, Gang; Chu, Zhong; Wang, Haoran; Liu, Xueqing; Zhu, Xin; Wang, Binzhong; Guo, Baifu; Wang, Runqiu; et al. (Frontiers in Marine Science, 2024)
Introduction Our understanding of the regulatory mechanisms that govern the development of sexual characteristics in sturgeon, particularly the Chinese sturgeon (Acipenser sinensis), is limited. Foxl2, a member of the forkhead/HNF-3-related transcription factor family, is known for its role in precise gene regulation within specific tissues and its control over ovarian aromatase, a key enzyme in ovarian development and maturation. This study aimed to investigate the sexually dimorphic expression of foxl2 during the molecular and morphological sex differentiation stages in Chinese sturgeon. Methods We successfully isolated the full-length cDNAs of foxl2 in Chinese sturgeon. We then examined the expression profiles of this gene across various somatic tissues in both female and male specimens. Results Foxl2 was predominantly expressed in the ovulatory organs of two-year-old Chinese sturgeon, with significantly lower expression in other somatic tissues. We observed sexual dimorphism in foxl2 expression within gonads that had achieved morphological differentiation. Discussion The results suggest that foxl2 expression is intricately linked to the process of ovarian differentiation in Chinese sturgeon. Furthermore, we propose that the mRNA quantities of foxl2 could serve as an accurate biomarker for sex determination in sturgeon during their early growth stages.